ANALISIS NILAI-NILAI BUDAYA DALAM NOVEL SI ANAK CAHAYA KARYA TERE LIYE - Pratiwi, Kelsy; Priyadi, Antonius Totok; Seli, Sesillia (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
The objective of this study is to provide a description of the cultural values depicted in the novel Si Anak Cahaya by Tere Liye, as well as to examine the extent to which these cultural values are incorporated into the learning behavior of students studying Bahasa Indonesia at the senior high school level (SMA/MA). The employed research methodology is the descriptive method, specifically utilizing a approach. The methodology employed in this study is the sociological approach to literature. The primary data source utilized in this study is the literary work entitled "Si Anak Cahaya" authored by Tere Liye. The data collection procedures employed in this study encompassed documentary investigations, which were afterwards examined by the researcher. Data validity assessment approaches employ several methods such as observation persistence, triangulation, and reference adequacy to ensure the accuracy and reliability of the data. The present study focuses on the examination of cultural values depicted in the novel Si Anak Cahaya by Tere Liye. The research entails a comprehensive data analysis to identify the cultural values manifested in the portrayal of the human-God relationship. These values include obedience in worship, surrender to the divine, resilience in the face of adversity, and the constant remembrance of the divine presence. These values encompass obedience, closeness, mutual tolerance, love, mutual assistance, and deliberation. The interaction between humans and nature serves as a reflection of cultural values, particularly in terms of the comprehension and appreciation of the natural world